Unique aspects of the Islamic microfinance financing process experience of Baitul Maal Wa Tamwil in Indonesia - Wulandari, Permata; Kassim, Salina; Sulung, Liyu Adhi Kasari; Putri, Niken Iwani (Emerald Group Publishing Ltd., 2016)
Purpose - This paper aims to highlight on the unique aspects of Islamic microfinance based on the experience of Baitul Maal Wa Tamwil (BMT) in Indonesia.